Reliability analysis of the precision assembly process of a scaled stator can of the AP1000 reactor coolant pump. (March 2019) - Jiang, Wei; Liu, Huahan
In this study, a reliability model for the assembly process of a stator can on the stator core in the AP1000 reactor coolant pump in a reduced scale is developed. Firstly, the tube hydroforming-based stator can assembly method is reviewed briefly. In order to extract the factors affecting the assembly results, a numerical assembly model and an assembly experiment rig are established. Assembly results are predicted by numerical analysis and validated by experiment. A reliability model with the proposed corrected-partial least squares regression-response surface method (C-PLSR-RSM)-based system reliability method is developed. The model is applied to analyze the assembly reliability of the stator can, and the effects of failure dependency on the estimation accuracy of reliability, as well as the relationships between the assembly reliabilities and different single evaluation index. The results indicate that the reliability model is able to efficiently analyze the implicit stator can assembly problem. Failure correlation brings a negative correlation relationship between the different assembly performance functions.